Preponderance of enterovirus C in RD-L20B-cell-culture-negative stool samples from children diagnosed with acute flaccid paralysis in Nigeria (2017)
Recently, a reverse transcriptase semi-nested polymerase chain reaction (RT-snPCR) assay was recommended by the WHO for direct detection of enteroviruses in clinical specimens. In this study, we use this assay and a modification thereof to screen acute flaccid paralysis (AFP) samples that had previously tested negative for enteroviruses by the RD-L20B algorithm. Thirty paired stool suspensions collected in 2015 as part of the national AFP surveillance program in different states of Nigeria were analyzed in this study. The samples had previously tested negative for enteroviruses in the polio laboratory in accordance with the WHO-recommended RD-L20B-cellculture- based algorithm. Two samples that had previously been found to contain enteroviruses were included as positive controls. All samples were subjected to RNA extraction, the RT-snPCR assay and a modified version of the RT-snPCR. All amplicons were sequenced, and enteroviruses were identified using the enterovirus genotyping tool and phylogenetic analysis. Amplicons were recovered from the two controls and 50% (15/30) of the samples screened. Fourteen were successfully typed, of which, 7.1% (1/14), 21.4% (3/14), 64.3% (9/14) and 7.1% (1/14) were enterovirus (EV) -A, EV-B, EV-C and a mixture of EV-B and C (EV-C99 and E25), respectively. The two controls were identified as EV-C99 and coxsackievirus (CV) -A1, both of which belong to the species Enterovirus C. In one sample, poliovirus serotype 2 was detected and found to have the VP1 ILE143 variation and was therefore identified as a vaccine strain. The results of this study showed that significant proportion of enterovirus infections (including some with Sabin PV2) are being missed by the RD-L20B-cell-culture-based algorithm, thus highlighting the value of the RT-snPCR assay and its modifications. The circulation and preponderance of EV-C in Nigeria was also confirmed.